From struggle to strategy: emotional engagement and an emergent coping theory among Title I instrumental music educators - Baker, Heather Nichole (My University, 2026)
Using funding navigation as a lens, this dissertation investigates how instrumental music educators in Title I schools balance resourcefulness, resilience, and coping strategies. Title I schools, which serve high-need communities, often face chronic underfunding. This places substantial demands and emotional burdens on music educators striving to sustain high-quality programs with limited resources. Understanding how these educators navigate funding challenges and manage their emotional environment offers important insights for supporting teacher well-being, program sustainability, and equitable student access to music education. Through qualitative narrative inquiry, eight instrumental music educators from diverse Title I schools participated in semi-structured interviews. Data were analyzed in two coding cycles, first identifying emotional associations and then broader themes related to funding and coping. Findings reveal that educators often make substantial personal, financial, and emotional investments, and experience a wide range of emotions—pride, hope, frustration, stress, and isolation—directly tied to funding demands. Coping strategies included seeking external funding, strategic planning, support networks, professional development, boundary-setting, and, at times, maladaptive habits such as overwork. These findings highlight the hidden emotional and practical labor required to sustain music education in under-resourced settings. The study underscores the need for targeted professional development, increased funding transparency, and organizational support to promote educator well-being and program stability. By focusing on the experiences of Title I instrumental music educators, this research provides actionable recommendations for policymakers, administrators, and advocacy groups seeking to improve equity and support in music education.
Keywords: Music; Coping strategies; Emotion; Funding; Engagement; Funding